2020
DOI: 10.1039/c9an01969c
|View full text |Cite
|
Sign up to set email alerts
|

Electroenzymatic glutamate sensing at near the theoretical performance limit

Abstract: Optimized sensors will enable more accurate monitoring of glutamate signaling in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…For Glut released farther from the sensor surface, response is lower and broader. For distances greater than 30 μm, even with the 1-D simplifications that overestimate response, simulated response remains below the limit of detection (LOD), which has been determined experimentally as ∼0.7 μM for such sensors . However, this 1-D simulation cannot provide a quantitative prediction of the maximum sensor/release site separation distance that could give rise to a detectable signal, yet the sensor sampling distance likely is far less than the range for electrophysiological recordings (100–200 μm) .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…For Glut released farther from the sensor surface, response is lower and broader. For distances greater than 30 μm, even with the 1-D simplifications that overestimate response, simulated response remains below the limit of detection (LOD), which has been determined experimentally as ∼0.7 μM for such sensors . However, this 1-D simulation cannot provide a quantitative prediction of the maximum sensor/release site separation distance that could give rise to a detectable signal, yet the sensor sampling distance likely is far less than the range for electrophysiological recordings (100–200 μm) .…”
Section: Resultsmentioning
confidence: 89%
“…Although the transient, one-dimensional model employed is an approximation, it is known to be a reasonably good one for the description of transport to typical sensors with characteristic dimension >25 μm . The sensor parameters used in this study correspond to a theoretically optimized design of the sort shown in Figure with a sensitivity of 364 nA μM –1 cm –2 and a response time of 8 ms, whereas the best measured intrinsic response time (in the absence of external mass transfer resistance) is ∼80 ms . These simulation results therefore correspond to aspirational sensor performance metrics, yet they illustrate well the key issues encountered in the interpretation of sensor data in what may be the best-case scenario.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations